Preliminary report on human remains from Tell Masaikh and Tell Ashara. Season 2009* - Tomczyk, Jacek (Studia Ecologiae et Bioethicae, 2013)
The middle Euphrates valley (Syria) is a very interesting and important region for the history of Mesopotamia. The excavations are currently carried out at Tell Ashara and Tell Masaikh. The first site is primarily the remains of a Bronze Age (2700–1500 BC). At Tell Masaikh were discovered the remains of a settlement from the Chalcolithic (4500 BC), and the Middle Bronze Age, as well as a huge governor’s palace from the times of the Assyrian empire’s days of glory (800–650 BC). The paper is a summary of anthropological research conducted in 2009. We have been excavated 80 human skeletons (50 individuals from Tell Masikh, and 30 from Tell Ashara).